If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 92 = 9x + -13 Reorder the terms: 92 + 2x = 9x + -13 Reorder the terms: 92 + 2x = -13 + 9x Solving 92 + 2x = -13 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 92 + 2x + -9x = -13 + 9x + -9x Combine like terms: 2x + -9x = -7x 92 + -7x = -13 + 9x + -9x Combine like terms: 9x + -9x = 0 92 + -7x = -13 + 0 92 + -7x = -13 Add '-92' to each side of the equation. 92 + -92 + -7x = -13 + -92 Combine like terms: 92 + -92 = 0 0 + -7x = -13 + -92 -7x = -13 + -92 Combine like terms: -13 + -92 = -105 -7x = -105 Divide each side by '-7'. x = 15 Simplifying x = 15
| x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a | | d=7h+12 | | 8*a^2+3a-800=0 | | 8*a^2+3a+800=0 | | 2x^3-6x^2+5x+6=0 | | -12h+30=-4h-17 | | 4x=5y+33 | | 15-(5-x)=1 | | 6(1-7k)=40-8k | | 3+2v=-6v+3 | | 2*log(x^2)+log(x-1)=0 | | 2logx^2+logx-1=0 | | 3(p+7)=-33 | | -98=-7(4+b) | | 225x^2+9= | | 2n+6=34 | | x+31-1=21 |